Educational technologies based on artificial intelligence in professional oriented foreign language education (Journal of Educational Sciences, 2024)
In recent years, the development of the scientific direction of artificial intelligence research has opened up new opportunities for transformations in various areas of human life, including foreign language education. This article is dedicated to educational technologies based on artificial intelligence in professionally oriented foreign language education. An analysis of the influence of the latest teaching technologies, developed on the basis of artificial intelligence, on the results of learning a foreign language will reveal its advantages and disadvantages of implementation in foreign language education. With an emphasis on professionally oriented foreign language education, the study determines how learning technologies based on artificial intelligence contribute to personalized foreign language learning and the development of professional communicative competencies. The article also explores the dynamic landscape of artificial intelligence in language education, comparing innovative platforms and applications that meet the specific needs of future professionals. By analyzing empirical data, theoretical foundations, survey and interview results, this study provides information about the effectiveness of implementation of artificial intelligence into the foreign language education of future professionals. A survey of 175 1st and 2nd year students was conducted on the use of AI and assignment completion. In addition, the study examines the prospects for research in this direction and possible limitations of the integration of artificial intelligence into foreign language education, focused on the professional training of future specialists. The practical implications of the results of the work include recommendations for teachers and stakeholders for the effective inclusion of artificial intelligence in the foreign language education curriculum.Key words: Artificial intelligence, Foreign language education, Professionally oriented level, Educational technologies